Bersinar di Era Digital: Strategi Manajemen Berbahasa Indonesia untuk Meningkatkan Minat Generasi Milenial dan Gen-Z - Anisa, Resha Yanur; Rahmi, Aisyah Alya; Haniyah, Siti Muanah; Agustiani, Fauziah Nur; Pajriati, Nur; Rizkyanfi, Mochamad Whilky (Indo-MathEdu Intellectuals Journal, 2024)
Technology has an important role in today's digital era. The existence of the digital era increases communication skills, it is important for Indonesian management to continue to innovate and adapt the use of technology in order to effectively attract and influence millennials and gen-Z who are active in digital platforms. The method used was qualitative by conducting interviews with three banking employees in the city of Bandung. The collected data are analyzed, reduced, presented and conclusions drawn. The results showed that there is a link between the success of the company and effective Indonesian-language management. Understanding consumers, especially to attract millennials and gen-Z, can be done by improving services by utilizing digitalization. The service digitalization strategy was developed to facilitate consumers and improve the company in market competition. The use of EYD-compliant Indonesian makes it easier for consumers to understand the service and avoid misunderstandings. Good service, structured Indonesian-language management shows a professional company image and is trusted by consumers. Research is expected to increase the use of good and correct Indonesian in a company when providing information to consumers and increase the attractiveness and involvement of millennials and gen-Z as consumers